PENERAPAN MODEL KOOPERATIF TIPE TGT BERBANTUAN MEDIA DIORAMA DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS XI IPA DI SMA - Kambu Ipu, Desry; Makaborang, Yohana; Louise Makatita, Audrey (Jurnal Biogenerasi, 2024)
Hadakamili Village, Wulla Waijelu District, East Sumba Regency. The aim of the research was to determine whether the application of the TGT type cooperative learning model can improve learning activities and student learning outcomes in Biology Subject Class The research procedure used in this research is classroom action research developed by Kemmis and Mc Taggart which is carried out in cycles and each cycle consists of the stages plan (planning), act (implementation), observe (observation) and reflect (reflection). Data collection techniques in this research include observation sheet data on learning activities, tests, and documentation. The data analysis used in this research is quantitative descriptive. The research subjects were students of SMA Negeri 1 Wulla Waijelu class X1 MIA with a total of 30 people. The research results obtained from the application of the TGT type cooperative learning model assisted by diorama media in increasing learning activities and learning outcomes for class Student learning activity was obtained at 76% and in cycle II student learning activity increased to 96%. Thus, the learning outcomes in cycle I obtained a pretest score of 65.33, posttest 72.25 and a final score of 70 reaching 46.67%. Then, there was an increase in cycle II, the pretest score was 74.33, the posttest was 83 and the final score was 80 with classical completion of 96.96%. Based on these results, it can be concluded that the application of the TGT type cooperative learning model assisted by diorama media can improve the activities and learning outcomes of class XI students in high school.